2013
DOI: 10.1016/j.nbd.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Regional vulnerability in Huntington's disease: fMRI-guided molecular analysis in patients and a mouse model of disease

Abstract: Although the huntingtin gene is expressed in brain throughout life, phenotypically Huntington's disease (HD) begins only in midlife to affect specific brain regions. Here, to investigate regional vulnerability in the disease, we used functional magnetic resonance imaging (fMRI) to translationally link studies in patients with a mouse model of disease. Using fMRI, we mapped cerebral blood volume (CBV) in three groups: HD patients, symptom-free carriers of the huntingtin genetic mutation, and age-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
(83 reference statements)
0
13
1
Order By: Relevance
“…These could be classified into six Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, confirming the observed alterations in metabolic pathways ( 38 ) and further identifying changes in axon sprouting and neurodegenerative pathways ( Dataset S2 ). These studies revealed an additional down-regulated regulatory subunit of protein phosphatase 1 (PPP1R7) ( 39 , 40 ). Taken together, these data reveal imbalances in dopaminergic and glutamatergic pathways in the early postnatal period of tgHD rats sufficient to explain the behavioral phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…These could be classified into six Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, confirming the observed alterations in metabolic pathways ( 38 ) and further identifying changes in axon sprouting and neurodegenerative pathways ( Dataset S2 ). These studies revealed an additional down-regulated regulatory subunit of protein phosphatase 1 (PPP1R7) ( 39 , 40 ). Taken together, these data reveal imbalances in dopaminergic and glutamatergic pathways in the early postnatal period of tgHD rats sufficient to explain the behavioral phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of preclinical neuroscience work is performed on transgenic rodent models for neurodegenerative diseases such as: AD, PD, and HD, which are characterized by deposition of misfolded proteins (proteinopathies) in the brain. In AD and HD, the presence of amyloid plaques and huntingtin, respectively, are hypothesized to affect cortical functioning as shown by diminished fMRI responses to sensory stimuli ( Lewandowski et al, 2013 ; Sanganahalli et al, 2013 ; see Figure 8 for an example). Moreover, entire neuronal networks seem affected ( Liu et al, 2014 ), as shown by altered functional connectivity during rsfMRI ( Shah et al, 2013 ; Ferris et al, 2014 ; Figure 9 ) even in early disease stages before the proteinopathy establishes ( Grandjean et al, 2014b ).…”
Section: Fmri Applications With Relevance For Pharmacological Researcmentioning
confidence: 99%
“…Interestingly, LXN was previously shown to be an important regulator of hematopoiesis [31-33], while deficiencies in peripheral blood functions of HD patients have been widely reported, including immune responses [34-36]. Furthermore, the Wnt signaling cascade, which FZD8 is a component of, is increasingly being reported as an important regulator of the cellular responses to mHTT in HD [37-39]. Transcriptome changes in human HD patients can be significantly influenced by other co-existing pathology unrelated to HD, which arguably would be a less pervasive influence in HD monkeys.…”
Section: Discussionmentioning
confidence: 99%